Fibrogenesis and carcinoid tumor - a case report - Alves Filho,Eduardo Fonseca (2012)
Carcinoid tumors are rare. They may appear in the entire gastrointestinal and respiratory tracts, with single or multiple occurrences. Prognosis is dependent on the size and location. Symptoms may appear in carcinoid syndrome, related to active substances, especially serotonin. One important aspect associated with these tumors and usually ignored is fibrogenesis. This is a case report of a patient with carcinoid tumor of the terminal ileum, treated by laparoscopy, associated with fat and fibrosis infiltration.